CRIMINAL LAW AND PSYCHOLOGY – CONNECTION POINTS - Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In the paper the author discovers and analyzes areas which represent points of connection between criminal law and psychology, the areas in which cooperation between these two fields of science is possible and desirable. This article is divided into several sections. Firstly, the author talks about the emergence of psychology as a science and its definition. In the sections that follow the author offers analysis of initial contact between ways of thinking in primeval criminal law and psychology, followed by analysis of development of this relationship after the official contact of these two fields in the area of criminal legislature and criminal trial. In the end, the author concludes that psychology is inseparably woven into the criminal law method of reasoning and that the knowledge of psychology is a precondition of a successful practical application of the criminal law.